The relationship between childhood obesity and male puberty development: a systematic review and meta-analysis - Feng, Wenhua; Ren, Chaonan (Frontiers in Endocrinology, 2025)
ObjectiveThis meta-analysis aimed to investigate the risks and physiological development differences during puberty in overweight and obese boys.MethodsFollowing the PRISMA 2020 guidelines and AMSTAR criteria, we systematically searched PubMed, EMBASE, and Web of Science, with a cutoff date of July 2025. After applying strict inclusion and exclusion criteria and performing quality assessments, statistical analysis was conducted using STATA 17.0 and Review Manager (version 5.4).ResultsA total of 12 prospective cohort studies meeting the inclusion and exclusion criteria were included in the analysis. The meta-analysis indicated that overweight boys had a significantly higher risk of early testicular enlargement compared to normal-weight boys (overweight RR 1.38, obese RR 1.43). Regional differences were observed, with significant variations in the association between overweight status and early testicular enlargement risk in the U.S. and Asia-Pacific regions. Overweight and obese boys older than 6 years had a stronger association with early testicular enlargement. Furthermore, overweight boys experienced an earlier onset of early testicular enlargement compared to normal-weight boys (MD -0.23, p=0.002), while no significant difference was observed in obese boys (MD -0.23, p=0.10). In terms of pubic hair development, overweight (RR 1.24, p<0.00001) and obese boys (RR 1.42, p<0.00001) were at a higher risk for early development, and overweight boys developed pubic hair earlier (MD -0.38, p=0.0008). No significant difference was found in peak height velocity between obese and normal-weight boys (MD -0.32, p=0.09).ConclusionOverweight and obesity have notable effects on male puberty development, particularly with respect to early testicular enlargement and pubic hair development.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier, CRD420251172699.